Analysis of the Effect of the Gini Ratio, Unemployment Rate, and Population Size on Economic Growth in North Sumatra Province - Tri Ade Mardinata; Suhendi; Rahmad Sembiring (CV. Era Digital Nusantara, 2026)
The purpose of this study is to examine whether the Gini ratio, unemployment rate, and population size have a significant effect on economic growth in North Sumatra Province during the period 2015–2024, both simultaneously and partially. This research was conducted using secondary/quantitative data published on the website of the Badan Pusat Statistik (BPS) of North Sumatra Province. The study aims to analyze both the simultaneous and partial effects in the relationship between the independent variables (X) and the dependent variable (Y). The results show that simultaneously, the Gini ratio, unemployment rate, and population size have a significant effect on economic growth in North Sumatra Province. Partially, the unemployment rate has a negative and significant effect on economic growth, while the Gini ratio and population size have positive but insignificant effects on economic growth in North Sumatra Province. This study is expected to contribute to public literature, serve as a reference for future research, and provide considerations for the government in policy decision-making.